Novas configurações de antenas, filtros e FSS com fractais de fuga no tempo para aplicações em microondas e ondas milimétricas - Minervino, Diego Ramalho (2017)
In this work, new configurations of devices and circuits of millimeter waves and microwaves with fracturing configurations of escape-time are investigated and proposed, such as the Julia and Mandelbrot sets, which are structures defined by a recurrence relation of each point in space. Specifically, it will be investigated the distribution of currents on the surfaces of filter conductors, planar antennas and frequency selective surfaces (FSS) with the considered fractal geometries, for applications in both wireless communication systems and systems in millimeter waves, in the frequency range between 0.7 and 30 (GHz). Transmission planar structures such as the microstrip lines and the coplanar waveguide (CPW) were considered in the development of filters and antennas with Euclidean and fractal geometries for microwave and millimeter wave applications. The choice of microstrip line structures for the development of new antenna and filter configurations is justified by the wide application of these transmission lines, always resulting in the manufacture of flat circuits with small structures, low cost, easy to construct and especially easy to integrate with other microwave and millimeter wave circuits. The great interest in applications in the millimeter wave range is associated to the growth of the use in the L and S bands, the speed of transmission between circuits, wireless communications systems and the reduction of components for use in wavelengths and millimeter waves. Initially, the study of time-fracturing fracturing was focused on microwave applications in antennas fed by coaxial cable and CPW. Finally, simulations, measurements and constructions of prototypes of antennas, filters and FSSs were carried out to validate the work done in this doctoral thesis.